OBESITY AS A RISK FACTOR FOR ENDOMETRIAL PATHOLOGICAL CHANGES - Kocevska, Ana; Pushevska, Anamarija Shpisikj; Ilievski, Zoran; Kitanova, Aleksandra Eftimova; Skeparovska, Kristina (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
According to the World Health Organization, overweight and obesity are defined as abnormal or excessive fat accumulation that may impair health. A body mass index (BMI) over 25 is considered overweight, and over 30 is obese. The elevated BMI is a major risk factor for cardiovascular diseases, diabetes, osteoarthritis, some cancers (endometrial, breast, ovarian, prostate, liver, gallbladder, kidney and colon). The most common cause of endometrial hyperplasia is high level of estrogens, combined with insufficient levels of progesterone, which causes secretory changes in the proliferated endometrium from estrogens. This excess endogenous estrogen stimulation can stimulate endometrial proliferation resulting in endometrial hyperplasia and endometrial cancer. The study included a total of 160 respondents. The study group consisted of 120 patients who underwent fractionated explorative curettage due to a medical indication. They were divided into two subgroups: perimenopausal and postmenopausal. The control group consisted of 40 healthy women without fractionated explorative curettage. Anamnestic data were taken from all respondents. Body weight, height and waist circumference were measured in all of the participants. We divided the patients with fractionated explorative curettage into 2 subgroups: with functional and organic changes changes of the endometrium.Patients with explorative curettage had a significantly higher BMI and waist circumference than healthy women. Postmenopausal women had a significantly higher BMI and waist circumference than perimenopausal women. Patients with organic endometrial changes had a significantly higher BMI and waist circumference compared to those with functional changes. Key words: obesity, endometrial, explorative curettage